1998
DOI: 10.1007/bf02465772
|View full text |Cite
|
Sign up to set email alerts
|

Amides and hydrazides of aroylpyrivic acids. Part 6 Synthesis and study of antiinflammatory and analgesic activity of β-aroylpyruvoyl hydrazides of 2-methyl(phenyl)-4-quinolinecarboxylic acids

Abstract: Previously we have demonstrated that 4-quinolinecarboxylic acid amides and hydrazides, substituted at position 2, exhibit pronounced antiinflammatory and analgesic activity at a quite low toxicity [1 -5]. It was established that the charaeter and strength of the pharmacological action depend on the type of substituents at positions 2 and 4 of the quinoline cycle.As is known, introduction of the aroylpyruvoyl fragment into amides and hydrazides imparts to them a high antiinflammatory and analgesic activity [6,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…These endonucleolytic cleavage of DNA by metal complexes are used as models for the reactivity of some antitumor antibiotics. Previously some work demonstrated that 4-quinolinecarboxylic acid amides and hydrazides, exhibit pronounced antiinflammatory and analgesic activity at a quite low toxicity [8][9][10][11][12], but no metal complexes of such drug have been reported in the past which may have better pharmaceutical effect. Therefore, studies of the metal complexes are important to explore the possible new drug compare with the present drug.…”
Section: Introductionmentioning
confidence: 99%
“…These endonucleolytic cleavage of DNA by metal complexes are used as models for the reactivity of some antitumor antibiotics. Previously some work demonstrated that 4-quinolinecarboxylic acid amides and hydrazides, exhibit pronounced antiinflammatory and analgesic activity at a quite low toxicity [8][9][10][11][12], but no metal complexes of such drug have been reported in the past which may have better pharmaceutical effect. Therefore, studies of the metal complexes are important to explore the possible new drug compare with the present drug.…”
Section: Introductionmentioning
confidence: 99%
“…Molarities of calf thymus DNA solutions were confirmed by spectrophotometric analysis (assuming ε 260 =6,600 M −1 cm −1 [16]). The ratio of absorbance at 260 and 280 nm was determined to verify solution purity, and a ratio between 1.7 and 2.0 was taken to indicate that the DNA samples were satisfactorily free of protein [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…The coordination compounds of aroylhydrazones have been reported to act as enzyme inhibitors [13] and are useful due to their pharmacological applications [14][15][16]. Previously, some work demonstrated that 4-quinolinecarboxylic acid amides and hydrazides, substituted at position 2, exhibit pronounced anti-inflammatory and analgesic activity at a quite low toxicity [17][18][19][20][21], but no metal complexes of such drugs have been reported in the past which might possibly have better pharmaceutical effect. Therefore, studies of the metal complexes are important in the search for new drugs.…”
Section: Introductionmentioning
confidence: 99%